Fetal complications of obstetric cholestasis. Issue 6014 (10th April 1976) - Reid, R; Ivey, K J; Rencoret, R H; Storey, B
Abstract : Among 56 pregnancies complicated by obstetric cholestasis five intrauterine deaths and one neonatal death occurred between 33 and 39 weeks, and a further six infants required urgent delivery for intrapartum asphyxia. Eighteen spontaneous premature deliveries occurred. Five mothers required specific treatment for unexplained postpartum haemorrhage. Cholestasis of pregnancy is therefore not a condition benign to the fetus, and it may contribute to increased maternal morbidity.